Korean Pop (K-Pop) Culture Phenomenon On The Behavior Of Indonesian Society - I Gusti Ngurah Jayanti; I Komang Arba Wirawan; Nyoman Lia Susanthi; Ni Wayan Masyuni Sujayanthi (Journal of Art, Film, Television, Animation, Games and Technology, 2022)
This study aims to analyze the phenomenon of K-pop culture in Indonesian society. The K-pop phenomenon has grown and become popular since the 1990s until now. K-pop is increasingly widespread as its fans come of any age and social status. Korean contents ranging from music, films, cuisine, and lifestyle, are increasingly popular and favored by the people of Indonesia. This has become a phenomenon that describes the massive diffusion of Korean culture that has had an impact on the lives of Indonesian people. The problems raised in this paper include 1). How the Indonesian people respond to the phenomenon of pop culture (K-pop); 2). How is the influence of cultural elements (K-pop content) on the behavior of Indonesian people. This study uses the triangulation method, namely observation, interviews, and documentation, while the analysis technique is descriptive and interpretive. The theory used to dissect the problem is a cultural theory, namely the theory of pop culture. The results of the research in this paper show that the influence of pop culture is a world phenomenon that occurs due to the influence of globalization; moreover, the progress of science and information technology influences people's consumption. The spread of the dominant culture is rapidly and massively diffused in the public and private spheres. Consumerism culture is something that seems commonplace in the phenomenon of pop culture, both among young people and adults. Pop culture (K-pop), which is trending (viral) among the Indonesian people, influences the behavior of the people. The lifestyle that imitates the models of K-pop is increasingly widespread, and some young people make K-pop a role model for their fashion and identity. The K-pop phenomenon certainly brings consequences to the cultural life of the Indonesian nation.